Epidemiology of non-fatal burn injuries in children: evidence from Bangladesh Health and Injury Survey 2016. Issue 1 (14th June 2022) - Abedin, Minhazul; Rahman, Farah Naz; Rakhshanda, Shagoofa; Mashreky, Saidur Rahman; Rahman, A K M Fazlur; Hossain, Ahmed
Abstract : Background: Burn is a major cause of childhood injury-related morbidity and mortality. Global estimates suggest that 90% of all cases occur in low-income and middle-income countries and over half of the disability-adjusted life-years are lost from fire-related burns in children. In Bangladesh, there is a scarcity of data on childhood burn injuries. The goal of the study was to describe the epidemiology of non-fatal burns in Bangladeshi children, including incidence estimates and identify high-risk groups. Methods: Bangladesh Health and Injury Survey 2016 was a large scale cross-sectional survey. The survey was conducted among 299 216 population utilising a multistage cluster sampling method. Among the 100 842 children, there were 437 non-fatal burn cases. Results: Among different injury mechanisms in children, burn was ranked fifth (7.4%). The overall yearly incidence rate (IR) of burns was 866.7 per 100 000 children (95% CI 785.6 to 947.8) in Bangladesh. The incidence was highest among 1–4 years old children (IR 2028.3, 95% CI 1761.1 to 2334.7) and had a 3.5 times higher risk of burns compared with the 15–17 years age group. Females had a much higher IR of non-fatal burns than males between the ages of 10–15 years (1655.2 vs 482.2). About 70% of burns occurred in rural areas. Hot liquid (44.7%), flames (32.5%) and hot objects (20.7%) were identified as the main causes of burns. The kitchen (60.9%), yards (20.8%) and bedroom and living room (10.5%) were the three most common places for burns. According to the study, 34.8% of burn incidences occurred between the hours of 7:00 and 10:00. Conclusion: Children in Bangladesh suffer from a high rate of non-fatal burns. The high-risk category was identified as preschool-aged boys and adolescent girls. The majority of the incidents occurred in the morning and inside the kitchen. These findings will help raise awareness and create intervention measures to reduce the high incidence of non-fatal childhood burns in Bangladesh.